In-silico study: Hm86 protein of Hyalomma marginatum (Ixodida) as a candidate to provide anti-tick vaccine - Marziae Shahriari-Namadi; Kourosh Azizi; Hamzeh Alipour (Scientific Reports)
Abstract Hyalomma marginatum is a major vector of Crimean-Congo hemorrhagic fever virus in Iran, posing serious threats to public health and livestock. With no effective vaccine currently available, recent studies have focused on identifying molecular targets for anti-tick vaccine development. This study investigates the HM86 protein through in-silico analysis to assess its potential as a vaccine candidate against H. marginatum. Hyalomma marginatum Hm86 protein was used to predict B-cell epitopes, assess sensitization, disulfide bond, physicochemical properties, allergenicity, and protein docking using online immunoinformatic servers. In silico analysis of the recombinant vaccine, based on an antigenic score of 0.7402, it was selected as a potential promising recombinant vaccine candidate. Docking was performed to determine the interaction between TLR2 and the Hm86 construct. The results indicated that the Hm86 gene possesses favorable immunogenic properties, is soluble, and effectively stimulates MHC class I pathways. Molecular docking between the modeled TLR2 receptor and the Hm86 protein revealed binding energies ranging from − 283.23 to − 242.95 kcal/mol and RMSD values between 81.50 and 96.50 Å. Notably, five residues of Hm86—B-GLU-172, B-TRP-144, B-ASN-174, B-THR-189, and B-THR-131—showed strong interactions with TLR2 through electrostatic forces, hydrophobic contacts, and multiple hydrogen bonds. These findings support the feasibility of Hm86 as an immunologically effective in-silico vaccine candidate for the control of H. marginatum.